1991
DOI: 10.1002/j.1460-2075.1991.tb07766.x
|View full text |Cite
|
Sign up to set email alerts
|

xUBF and Rib 1 are both required for formation of a stable polymerase I promoter complex in X. laevis.

Abstract: We show that three protein fractions are required for accurate transcription initiation at a Xenopus laevis ribosomal gene promoter in vitro: RNA polymerase I, Rib1 and xUBF. The Rib1 and xUBF fractions are both necessary and sufficient for formation of a stable initiation complex. The xUBF fraction can be completely replaced by recombinant xUBF. We also report the sequence of a cDNA clone for xUBF. xUBF is 701 amino acids in length, contains domain which are related to a domain found in chromosomal proteins H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
147
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(150 citation statements)
references
References 30 publications
3
147
0
Order By: Relevance
“…TIF-IB has been shown to consist of TBP and 3 pol Ispecific TAFs [39]. Ribl appears to be its Xenopus equivalent but has not been molecularly characterized [40]. These observations raised the possibility that DNA-PK phosphorylates and inactivates a polypeptide in the promoter-bound TBP-TAF complex.…”
Section: Discussionmentioning
confidence: 99%
“…TIF-IB has been shown to consist of TBP and 3 pol Ispecific TAFs [39]. Ribl appears to be its Xenopus equivalent but has not been molecularly characterized [40]. These observations raised the possibility that DNA-PK phosphorylates and inactivates a polypeptide in the promoter-bound TBP-TAF complex.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, UBF is a likely candidate because we have shown that it is clearly a sequence-tolerant protein previously shown to produce discrete footprints on the promoters of all vertebrate species examined (7,(12)(13)(14)33). In addition, UBF can functionally substitute across species boundaries in some cases (13,14), and it is apparently involved in recruiting or stabilizing the TBP-containing activity in transcription complexes on the promoter (10,13,18,33,34,53).…”
Section: Methodsmentioning
confidence: 96%
“…UBF was originally purified by two independent means, first as a human cell fraction necessary for RNA polymerase I transcription in vitro and as an rRNA gene enhancer binding protein (10)(11)(12). UBF has now been purified and cloned from human, frog, rat and mouse (7,(13)(14)(15)(16)(17)(18)(19)(20). The UBF protein consists of an amino terminal dimerization domain (19, 21,22) followed by five repeated 80 amino acid domains (17) termed HMG-boxes due to their similarity to the DNA binding domains of High Mobility Group (HMG) proteins 1 and 2 (16), and a highly acidic carboxyl terminal tail.…”
mentioning
confidence: 99%
See 2 more Smart Citations